GPU-accelerated computational study of block copolymer self-assembly with advanced polymer theories - He, Juntong, author; Wang, Qiang, advisor; Prasad, Ashok, committee member; Bailey, Travis, committee member; Gelfand, Martin, committee member (Colorado State University. Libraries, 2024)
A high-performance GPU-accelerated software package for self-consistent field (SCF) calculations of block copolymer assembly, PSCF+, has been developed. PSCF+ allows various combinations of chain-connectivity models (including the continuous Gaussian chains, discrete Gaussian chains, and freely jointed chains), non-bonded isotropic pair (including the Dirac δ-function, soft-sphere, dissipative particle dynamics, and Gaussian) potentials and system compressibility (incompressible vs. compressible). The Richardson-extrapolated pseudo-spectral methods, the crystallographic fast Fourier transform, the "slice" algorithm, and the automated calculation-along-a-path are implemented in PSCF+, which not only speed up the SCF calculations and reduce the GPU memory usage significantly, but also make it very efficient in constructing phase diagrams. Given the wide use and great success of SCF calculations in understanding and predicting the self-assembled structures of block copolymer, PSCF+ will be an invaluable computational tool for the polymer community. Using PSCF+, we studied the stability of various Frank-Kasper phases formed by neat diblock copolymer (DBC) A-B melts using the "standard" model and the dissipative particle dynamics chain model and found that in general the SCF phase diagrams of these two models are qualitatively the same but with important differences. We also studied the stability of various Frank-Kasper phases formed by binary DBC blends using the "standard" model and found that the relative stability among the Frank-Kasper phases is dominated by their internal-energy densities. Finally, we performed high-accuracy SCF calculations to study the stability of all known tiling patterns formed by symmetrically interacting ABC miktoarm star triblock terpolymers.
Keywords: polymers; consistent field theory; self-assembly